Determination of Soil Parameters to Analyze Mechanical Behavior Using Lade's Double-Surface Work-Hardening Model. Issue 5 (3rd July 2016) - Oh, Sewook; Kwon, Youngcheul; Seo, Junwon
Abstract : In this study, Lade's double-surface work-hardening constitutive model was adopted which uses the elasto-plasticity model as a basic conceptual framework. The model can analyze work hardening and work softening of nonlinear stress-strain behavior, and is regarded as superior to other elasto-plasticity constitutive models in terms of estimation. In the double-surface work-hardening constitutive model, 14 soil parameters are needed to estimate soil behaviors. To determine them, laboratory tests—isotropical consolidation test and conventional compression test—were conducted. Determining of soil parameters is highly complicated and time-consuming; randomness cannot be ruled out in determining parameters that are sensitive to stress-strain estimation, and error may occur. For this reason, a linear and nonlinear regression analysis was used to determine soil parameters. In estimation of undrained behavior, the estimated stress-strain behavior based on the two constitutive models largely overlapped with the test results. However, in estimating drained behavior, the outcome of the two models and the test results were mostly the same, but between the two models, the double-surface work-hardening constitutive model had a sharper slope in initial stress state, and a smaller maximum deviatoric stress.